A mixed methods exploration of "Creativity in Mind", an online creativity-based intervention for low mood and anxiety. (2nd November 2021) - Tribe, Rachel H.; Alcock, Kat; Scior, Katrina; Huddy, Vyv
Abstract: Background: Within the current context of a global pandemic, the value of the Internet has been greatly elevated for many people. This study is an investigation into a 30-day online intervention called Creativity in Mind (CIM). Aims: To provide a preliminary indication of the relationship between participation in CIM and change in mood symptoms and wellbeing. Methods: A co-produced mixed methods design was used to evaluate CIM. Data was obtained from 55 participants. Each day for 30 days participants received a predetermined creative challenge that they were encouraged to complete and share within the group. Measures of mood and wellbeing were collected at three time points, including a 3-month follow-up. Qualitative interviews were undertaken with 18 participants and analysed using framework analysis. Results: Scores on mood and wellbeing measures showed an overall significant improvement following completion of the programme. However, only a small number of participants demonstrated clinically significant improvement (14%) or deterioration (5%). The qualitative data indicated that CIM was experienced positively, with some negative emotions arising from the volume of interactions and negative comparisons made between participants. Conclusions: Preliminary results demonstrate that the pattern of clinically significant change across individual participants was comparable to other psychological therapy.